Justification of a recipe mixture based on whole oat grain for the production of minced meat products - Z. A. Bochkareva; E. E. Nikonova (Новые технологии, 2025)
Introduction. Application of plant additives into minced meat in order to increase the nutritional value of products has been justified in the article. A mixture of plant products based on whole oat grain has been proposed as an alternative to sing wheat bread in minced meat. The indicators of minced meat products containing different amounts of a mixture of whole oat grain, wheat bran and dried apples have been assessed.The goal of the research is to determine the possibility of using a mixture based on whole oat grain in developing recipes and technology for minced meat products to increase the nutritional value and expand the range of products.The methods. To create the mixture 60% of whole oat grain, 20% of wheat bran and 20% of dried crushed apples were used. To introduce the mixture based on whole oat grain into the minced meat, it was hydrated using water at a temperature of 15-20 °C in a ratio of 1:2 for 10-15 minutes. The objects of the research were 3 samples of minced meat products with 10%, 15% and 20% of the mixture based on whole oat grain.The results of the study of finished culinary products have shown that the lowest weight loss and higher nutritional value of the products compared to the prototype is in samples No. 2 and No. 3 with the addition of 15% and 20% of the mixture based on whole oat grain.